El control jurisdiccional de los actos de la administración pública: el contencioso administrativo - Moreno Guzmán, Lady Janet (2007)
The present work of Thesis, to opt the I Title of Lawyer, Titled: "THE JURISDICTIONAL CONTROL OF THE ACTS OF THE PUBLIC ADMINISTRATION: THE CONTENTIOUS one ADMINISTRATIVE", he/she heads to promote the importance of the new focus that the Law of the Contentious Administrative Nº 27584 and their modifications: 27709 and 28531; it has incorporated in the normative Peruvian; it is pointed out that he/she has spent of the Administrative Contentious Process, bounded to the revision of the legality of the administrative act, by means of the resource of nullity of the administrative act, to the resource of full jurisdiction, in which is not only requested to the tribunal the repeal of the act of the public administration, but the recognition of the right transgredido; in a same way it is guided to promote a critical reflection on the thematic of the test in the contentious one administrative, starting from the analysis of the theory of the test, establishing that the same one is justified in the administrative contentious processes, for what you/they should be acted in the judicial means the probatory means that have for purpose to generate conviction in the judge on the controversial and not alone facts, those that it is presented in the Administrative Procedure and this becomes more justifiable, if we have opted in the Contentious Peruvian, for the resource of full jurisdiction and not only for that of the nullity